2006
DOI: 10.1111/j.1526-4610.2006.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Receptor A –231 G>A Polymorphism: No Linkage to Primary Pediatric Headache

Abstract: Our study shows that the -231 G>A polymorphism in the EDNRA gene is neither associated with primary juvenile headache nor significantly correlated with main clinical features characteristic of the headache pathology in pediatric settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Interestingly, the potent vasoconstrictor endothelin (ET) 1, whose effect is mediated via ET type A and B receptors, has been shown as a potent inducer of CSD [Dreier et al, 2002]. However further studies have been undertaken in a pediatric Italian cohort investigating the same polymorphism, and failed to replicate the earlier positive association [Lisi et al, 2006].…”
Section: Vascular Genesmentioning
confidence: 99%
“…Interestingly, the potent vasoconstrictor endothelin (ET) 1, whose effect is mediated via ET type A and B receptors, has been shown as a potent inducer of CSD [Dreier et al, 2002]. However further studies have been undertaken in a pediatric Italian cohort investigating the same polymorphism, and failed to replicate the earlier positive association [Lisi et al, 2006].…”
Section: Vascular Genesmentioning
confidence: 99%
“…Our experience Given the increased familial risk in relatives of migraine probands, we have, among the genes shown to be associated to adult migraine liability, recently focused on whether the -231 G>A polymorphism in the endothelin 1 type A receptor (EDNRA) shown to strongly modulate the risk of adult migraine [13] contributes to paediatric migraine susceptibility. Results to date obtained, however, show that the -231 G>A polymorphism in the EDNRA gene is neither associated with primary juvenile headache nor significantly correlated with main clinical features characteristic of the headache pathology, thus suggesting the possibility of an age-related interaction of the EDNRA polymorphic variant on migraine liability and disease expression [14].…”
Section: Molecular Studies Of the Genetic Factors In Adult Migrainementioning
confidence: 79%
“…Goadsby and colleagues [1996] have also reported that ET does not play a significant role in the vasoconstrictor portion of the cerebral blood flow change seen in the spreading depression, nor does it affect the resting flow in an in vitro model using the middle cerebral artery, harvested from cats postmortem. Also in this respect, the ET A (-231 A/G) polymorphism, which was reported to be associated with migraine [Tzourio et al, 2001], was subsequently found to be neither associated with primary juvenile headache nor correlated with main clinical features characteristic of the headache pathology in pediatric settings [Lisi et al, 2006].…”
Section: Cgrp Sp and Nka Involvement In Migrainementioning
confidence: 96%